Molecular diversity of the cyclization reaction of 3-methyleneoxindoles with 2-(3, 4-dihydronaphthalen-1(2H)-ylidene)malononitriles. Issue 28 (29th February 2016) - Lu, Yu-Ling; Sun, Jing; Xie, Ya-Jing; Yan, Chao-Guo
Abstract : The cyclization reaction of 3-methyleneoxindoles with 2-(3, 4-dihydronaphthalen-1(2 H )-ylidene)malononitrile in ethanol in the presence of DBU at room temperature afforded functionalized 3′-iminospiro[indoline-3, 2′-phenanthrenes] in good yields. Abstract : The cyclization reaction of 3-methyleneoxindoles with 2-(3, 4-dihydronaphthalen-1(2 H )-ylidene)malononitrile in ethanol in the presence of DBU at room temperature afforded functionalized 3′-iminospiro[indoline-3, 2′-phenanthrenes] in good yields. However, the similar reaction of ethyl 2-cyano-2-(3, 4-dihydronaphthalen-1(2 H )-ylidene)acetate resulted in functionalized 3-oxospiro[indoline-3, 2′-phenanthrenes] and benzo[ d ]phenanthro[2, 3- f ][1, 3]diazepines depending on the structures of substrates. Furthermore, the cycloaddition reaction of 3-phenacylideneoxindole with ethyl 2-cyano-2-(3, 4-dihydronaphthalen-1(2 H )-ylidene)acetate produced the spiro[indoline-3, 2′-phenanthrene]-4′-carbonitrile derivatives. The stereochemistry of the cyclic spirooxindoles was clearly elucidated by 1 H NMR data and fourteen single crystal structures.